Effectiveness of Amaranthus gangeticus in Arsenic Extraction from Soil (Journal of Scientific Research, 2016)
Phytoremediation of heavy metal rich soil has become a practical approach nowadays. Though this method is very promising, it requires long time for complete remediation of contaminated soil. Assortment of appropriate plant for specific heavy metal is very important to decontaminate soil within short period of time. The present study was conducted on Amaranthus gangeticus, to find out its potential to remove arsenic (As) from soil within short period of time. Phytoremediation trail was followed by growing plants in varying concentrations of As contaminated soil and subsequently one month of plant growing period it removed 72%-81% of the total soil As. This species accomplish maximum accumulation capacity of 17934 mg/Kgin shoots and store 72%-78% metal in aerial parts. Several parameters that have an influence on phytoremediation potential such as time, concentration, bioconcentration factor (BCF) and translocation factor (TF) were also calculated to investigate its appropriateness as effective hyperaccumulator.